2018
DOI: 10.1016/j.jdent.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent perceptions of orthodontic treatment risks and risk information: A qualitative study

Abstract: Introduction: For effective risk communication, clinicians must understand patients' values and beliefs in relation to the risks of treatment. This qualitative study aimed to explore adolescent perceptions of orthodontic treatment risks and risk information. Methods: Five focus groups were carried out with 32 school/college pupils aged 12-18 in Wales, UK. Participants were purposively selected and had all experienced orthodontic treatment. A thematic approach was used for analysis and data collection was compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…38 The latter are less likely to consider their orthodontist's advice and change their dietary habits. 39,40 Patients may also find it difficult to follow their orthodontist's advice completely and change their dietary habits as they find the advice unrealistic. 40,41 The findings of this and previous studies highlight the importance of dealing with patients' expectations as well as reinforcing dietary advice through informed consent and constant reminders during follow-up visits.…”
Section: Discussionmentioning
confidence: 99%
“…38 The latter are less likely to consider their orthodontist's advice and change their dietary habits. 39,40 Patients may also find it difficult to follow their orthodontist's advice completely and change their dietary habits as they find the advice unrealistic. 40,41 The findings of this and previous studies highlight the importance of dealing with patients' expectations as well as reinforcing dietary advice through informed consent and constant reminders during follow-up visits.…”
Section: Discussionmentioning
confidence: 99%
“…One study that included fixed and functional/removable appliances, and retainers, found that young people reported restricted food choice and impacts on the eating process (Carter et al, 2015). Studies that investigated the lived experience of braces and retainers found some negative impacts including pain, difficulty eating and problems due to breakages (McNair et al, 2006; Perry et al, 2018). These authors argued that young people tolerate negative aspects because they are motivated by the benefits of undergoing treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It may also be prudent to revisit the consent process at particular time-points during the course of treatment to maintain the 'validity' of the consent. 28 This is particularly important as patients may progress from a 'pre-Gillick' state of competence to become Gillick competent in the 'eyes of the law', during the course of treatment.…”
Section: Social and Emotional Well-beingmentioning
confidence: 99%
“…1 Optimal patient-centred methods of assessing and describing risks are being explored. 28,44 Focus groups encourage communication between participants in order to explore people's knowledge, experiences and concerns. 13 The use of such groups has been shown to be an effective way of determining what information patients want regarding their health and available treatment options.…”
Section: Restorationsmentioning
confidence: 99%
See 1 more Smart Citation